Analysis of the Impact of Services and Consumer Trust on Consumer Loyalty in Using Services - Muammar Rinaldi; Ihdina Gustina; Dedy Lazuardi; Elisabeth Nainggolan (Enrichment : Journal of Management, 2022)
The purpose of this research is to determine the effect of Service and Consumer Trust on Consumer Loyalty at Prima Elektronik. The population in this research is consumers of Prima Elektronik totaling 1,498 respondents. The technique of determining the samples used in this research is the Slovin formula and totaling 94 respondents. The research method used is the technique of collecting data through library research conducted systematically based on research objectives. The analytical method is used to solve problems and prove hypotheses with descriptive analysis, and regression analysis. This analysis includes validity and reliability, classic assumption test, multiple regression analysis, hypothesis testing through t and F test, and test the coefficient of determination (R2). The t-test results show Service variable had a positive and significant on Consumer Loyalty at Prima Elektronik. The Consumer Trust variable had a positive and significant on Consumer Loyalty at Prima Elektronik. The F test results show that the independent variables Service and Consumer Trust adjusted for the variable Consumer Loyalty. Test results of the coefficient of determination (R2) indicate that the Consumer Loyalty variables are supported by Service and Consumer Trust variables.